A comparative study of treatment interventions for patellar tendinopathy: a secondary cost-effectiveness analysis. Issue 6 (December 2022) - Fernández-Sanchis, Daniel; López-Royo, María Pilar; Jiménez-Sánchez, Carolina; Herrero, Pablo; Gómez-Barrera, Manuel; Calvo, Sandra
Objective: To compare the cost-effectiveness of three patellar tendinopathy treatments. Design: Secondary (cost-effectiveness) analysis of a blinded, randomised controlled trial, with follow-up at 10 and 22 weeks. Settings: Recruitment was performed in sport clubs. The diagnosis and the intervention were carried out at San Jorge University. Participants: The participants were adults between 18 and 45 years (n = 48) with patellar tendinopathy. Interventions: Participants received percutaneous needle electrolysis, dry needling or sham needling, all of which were combined with eccentric exercise. Main outcome measures: Costs, quality-adjusted life years and incremental cost-effectiveness ratio were calculated for each group. Results: The total cost per session was similar in the three groups: €9.46 for the percutaneous needle electrolysis group; €9.44 for the dry needling group; and €8.96 for the sham group. The percutaneous needle electrolysis group presented better cost-effectiveness in terms of quality-adjusted life years and 96% and 93% probability of being cost-effective compared to the sham and dry needling groups, respectively. Conclusion: Our study shows that percutaneous needle electrolysis has a greater probability of being cost-effective than sham or dry needling treatment.